Discussion: A fuzzy classification process for swelling soils [Transp. Infrastruct. Geotechnol. 10(3), 474-487] - O'Kelly, Brendan (My University, 2024)
This communication article presents a discussion of various fundamental points pertaining to the Toksöz Hozatlıoğlu and Yılmaz (2023) (the Authors) investigation [published in Transp. Infrastruct. Geotechnol. 10(3), 474–487], specifically scrutinizing the practical ramifications of employing the liquid limit (LL) parameter (by itself) to infer soil expansivity. Based on previous experimental investigations and their own independent analyses presented in this article, the Discussers demonstrate that without proper consideration of soil mineralogical activity, the sole reliance on the LL parameter (as adopted in the Authors’ investigation) is often not a reliable basis for performing soil expansivity assessments. Accordingly, the LL-based fuzzy classification approach reported by the Authors, despite addressing potential uncertainties arising from LL determinations by the Casagrande percussion-cup method, would, in itself, not lead to significantly more reliable soil expansivity assessments. As a way forward, a practical and more realistic classification framework for expansive soils based on equilibrium sediment volume measurements is presented and compared to the LL-based scheme adopted in the Authors’ investigation. Through this endeavor, it is demonstrated that the sole reliance on the LL parameter generally produces overly conservative soil expansivity rankings.
PUBLISHED
Keywords: Expansive soil; Liquid limit; Plasticity index; Mineralogical activity; Equilibrium sediment volume; Smart & Sustainable Planet; Atterberg limits; FUZZY LOGIC; Geotechnical Engineering; Geotechnics; PLASTICITY; SOIL PROPERTIES; SOIL TYPE; Soil Mechanics; Soil Mechanics & Foundations; expansive clay; expansive soil; fine grained soil; geotechnical; liquid limit; soil classification; soil plasticity; soil shrinkage